2001
DOI: 10.1074/jbc.m101887200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interdomain Salt Bridges in the Pore-forming Ability of the Bacillus thuringiensis Toxins Cry1Aa and Cry1Ac

Abstract: linking domains I and II in Cry1Aa were abolished individually in ␣-helix 7 mutants D222A, R233A, R234A, and D242A. Two additional mutants targeting the fourth salt bridge (R265A) and the double mutant (D242A/R265A) were rapidly degraded during trypsin activation. Mutations were also introduced in the corresponding Cry1Ac salt bridge (D242E, D242K, D242N, and D242P), but only D242N and D242P could be produced. All toxins tested, except D242A, were shown by light-scattering experiments to permeabilize Manduca s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Experiments using N-methyl-D-glucamine were carried out only at pH 7.5, since this amine is not ionized at pH 10.5. As was reported earlier (8,31,32), the volume recovery values measured after 3 seconds in the presence of Cry1Aa are far superior in the presence of N-methyl-D-glucamine hydrochloride than in the presence of potassium gluconate as expected from the fact that the pores are cation selective (17). For all mutants, volume recovery was also much higher in the presence of N-methyl-D-glucamine hydrochloride (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Experiments using N-methyl-D-glucamine were carried out only at pH 7.5, since this amine is not ionized at pH 10.5. As was reported earlier (8,31,32), the volume recovery values measured after 3 seconds in the presence of Cry1Aa are far superior in the presence of N-methyl-D-glucamine hydrochloride than in the presence of potassium gluconate as expected from the fact that the pores are cation selective (17). For all mutants, volume recovery was also much higher in the presence of N-methyl-D-glucamine hydrochloride (Fig.…”
Section: Resultssupporting
confidence: 64%
“…However, Cry1Ac, which was slightly more toxic to M. sexta than Cry1Aa and Cry1Ab in previous studies (7,40), was slightly less toxic than Cry1Aa (Table 1). On the other hand, although Coux et al (7) 2 ) than those found in the present study, the activity of the Cry1Aa mutant that they observed was closer to that measured in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…The Cry1Aa mutant R233A was created by oligonucleotide-directed in vitro mutagenesis (7). The wild-type toxins Cry1Aa, Cry1Ab, Cry1Ac, Cry1Ba, Cry1Ca, and Cry1Ea and the R233A mutant were prepared from B. thuringiensis strains producing the appropriate single recombinant toxins as described elsewhere (23).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Cry1A toxins, the first 28 amino acid residues are removed from the N terminus and approximately half of the protoxin residues are removed from the C terminus (6). However, susceptibility of the activated toxins to further proteolysis in the midgut environment could possibly affect toxicity and explain apparent discrepancies that are occasionally observed between their in vitro and in vivo activities (15,41,49,60). For example, Cry1Ca can be completely degraded when incubated with midgut juice from advanced larval instars of Spodoptera littoralis (29).…”
mentioning
confidence: 99%